PATOGENISITAS CENDAWAN ENDOFIT Aspergillus Sp. DARI TANAMAN JAGUNG TERHADAP MORTALITAS Spodoptera frugiperda J.E Smith - Yahya, Ivonela Karolina (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2024)
Biological control using endophytic fungi is one solution that can be applied to prevent or reduce S. frugiperda pest attacks, especially in corn plantations. The purpose of this study was to determine the effect of pathogenicity test of endophytic fungus Aspergillus sp. from the exploration results that can cause mortality in Spodoptera frugiperda. This study with three stages, namely the first stage of taking test samples of S. frugiperda in corn fields and the second stage of colonization testing for one of the endophytic fungi obtained from the results of exploration of corn plants, then in the third stage a pathogenicity test was carried out using the completely randomized design (CRD) method using endophytic fungus Aspergillus sp and tested on three stages of S.frugiperda as a treatment with a spore density of 108/ml. The results of the study showed that the infection rate at the larval stage of S.frugiperda reached 55% up to a mortality rate of 52.5%, then observations at the infected pupal stage of S.frugiperda reached 27.5% and the mortality rate was up to 30% to cause mortality of 32.5% as well as at the observation stage infected imago were not much different from the results of observations of the pupal stage.